Structural and Spatial-Functional Changes in the Development of Enterprises in Ukraine - Ivan Burtnyak; Oleksandr Kusnir; Roman Kashevskyi (Journal of Vasyl Stefanyk Precarpathian National University)
This article compares the dynamics of changes in the number of enterprises in relation to the working-age population. The division of economic activities into main sectors is used. The main goal of this study is to analyze the growth rates of the number of enterprises and the structure of enterprises in sectors with different functional characteristics, which allows us to obtain information about the transformations that occur in the context of the above-mentioned issues. This also allows us to distinguish the processes of concentration and deconcentration of economic functions in accordance with their relative position in relation to the administrative hierarchy, the main regions of development or other structural and functional units, defined in terms of the specificity and intensity of spatial development. The results of the study indicate a decrease in the spatial dynamics of private enterprises, inertia, spatial polarization and mosaicism. It is extremely difficult to give detailed answers to the questions about the reasons for such a situation, given the current level of knowledge, but two approaches can be proposed. The first approach is confirmed by observations of periodic increases in demand, especially for agricultural land. Studies have shown that there are differences in the development of entrepreneurship depending on the field of activity and functional features of the municipality. Secondly, in the period after the war, the dynamics of the development of service facilities weakened, and the importance of the industrial and construction sectors increased. Municipalities were differentiated according to their geographical location and economic functions. The capital regions benefited the most. The situation on the periphery was more complicated. In more backward regions, remote from the war, the number of enterprises grew dynamically, especially in the industrial and construction sectors. The shortage of jobs in the country could be filled by creating enterprises by people who were previously unemployed or worked in related and non-related industries. Thus, the movement of enterprises and individuals providing construction and installation services will become a kind of hierarchy, when experienced workers will go abroad, and new ones will come to their place. Rapid growth of businesses in non-urban areas is particularly desirable from a regional development perspective.